O papel da leitura nas aulas de inglês: uma análise segundo a percepção dos professores do ensino médio de escolas públicas estaduais de Natal - Souza, Rudson Edson Gomes de (2010)
This dissertation aims at investigating the teachers beliefs about the role of the reading ability in English at public state high schools in Natal and identifying the social value of the process of learning English for students of a foreign language. From the understanding of studies on reading, both in the field of Cognitive Psychology, as in Gibson & Levin (1975), as in the area of Psycholinguistics, as in Goodman (1970) and Del Re (2006), We researched the teachers perceptions about the skills and competencies that should permeate their educational practices, through their knowledge about theories of language acquisition as Cognitivism (Piaget, 1961) and Social Interactionism (Vygotsky, 1979) and the official documents (PCNEM, 1999; PCN+, 2002 ) that are the parameters for teaching a foreign language. We took into consideration other factors that influence the choice of the goals and the objectives to be worked out, such as: intensity of teachers workload, number of classes and students per class for each teacher, materials and technologies available, among other factors that will play an important role in the choice of the appropriate methodologies. To conduct a case study, two questionnaires were used in the construction of direct interviews with fourteen English teachers in twenty schools. According to data on the teachers beliefs we could find that for them the reading ability does not seem to have an special treatment in the teaching of a foreign language due to factors that undermine this process and therefore make teachers do not realize the real objectives of teaching English at public state high schools in Natal. As a consequence, the current process of education complicates the formation of autonomous learners capable of fighting for a social transformation